2004
DOI: 10.1007/978-3-540-24732-6_10
|View full text |Cite
|
Sign up to set email alerts
|

Explicit State Model Checking with Hopper

Abstract: Abstract. The Murϕ-based Hopper tool is a general purpose explicit model checker. Hopper leverages Murϕ's class structure to implement new algorithms. Hopper differs from Murϕ in that it includes in its distribution published parallel and disk based algorithms, as well as several new algorithms. For example, Hopper includes parallel dynamic partitioning, cooperative parallel search for LTL violations and property-based guided search (parallel or sequential). We discuss Hopper in general and present a recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…There are two other parameterized subjects that have a low observed R-DFS error density: Airline with parameters (20,2) and Piper with parameters (2,16,8). These are interesting subjects because other parameterized versions of these models have a high observed R-DFS error density.…”
Section: Resultsmentioning
confidence: 99%
“…There are two other parameterized subjects that have a low observed R-DFS error density: Airline with parameters (20,2) and Piper with parameters (2,16,8). These are interesting subjects because other parameterized versions of these models have a high observed R-DFS error density.…”
Section: Resultsmentioning
confidence: 99%
“…This is a subject for future work. Experimental results for a guided-search algorithm, where randomization is used to select a successor among the first n elements in a priority queue, showed that X follows a normal distribution [10]. Increasing n was shown to increase both the variance and the mean of X. Randomization improved the search performance because the probability of observing a small value of X increased logarithmically with the variance, provided the mean remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…random walk) in model checking and reported on its benefits, including [14,7,18,10,15]. To the best of our knowledge, DRS is the first complete Las Vegas algorithm to be proposed for the problem.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid extensive duplication of previous work, older blocks are occasionally loaded for comparison. We have reimplemented and profiled the Mono and Local algorithms in Hopper [4]. Both algorithms were profiled on a collection of five model checking problems.…”
Section: Profiling Existing Uses Of Diskmentioning
confidence: 99%